PEMANFAATAN LIGNIN DARI LINDI HITAM UNTUK PEMBUATAN KOPOLIMER LIGNIN RESORSINOL FORMALDEHIDA SEBAGAI PEREKAT KAYU LAMINA - Adi Santoso (Jurnal Penelitian Hasil Hutan, 2004)
Black liquor as a waste of (yielded by) pulp factories in Indonesia was estimated to reach more than 2.3 million tonnes/year. The use of this liquid has long been explored for wood adhesive, particularlyfor glue cold setting type. In this research, black liquor was isolated to get lignin isolate by re-precipitation method. The lignin isolate was then added with resorcinol and formaldehyde at molar ratio of Lignin (L): Resorcinol (R): Formaldehyde (F) = 1:0.5:2. Physical. mechanical, and chemical properties of the glue were tested and evaluated using procedures described in Indonesian standard (SN/)and Japanese standard (JAS).Results indicated that the isolate lignin obtained from black liquor contained typical functional groups, namely hydroxyphenolic and  metoxyl. Under FTIR spectrophotometer. the co-polymer lignin resorcinol formaldehyde showed similar infrared wave number  to those of  phenol  resorcinol formaldehyde  resin. The adhesive  yielded from co-polymerization lignin had  a  red-brown colored dilution, typical phenol smell, with 48.95% of  solid content, 3. 71% of free formaldehyde,  and  227.5 minute of gelatinous time. The Lignin resorcinol formaldehyde glue is applicable for laminated  wood  products.